THE EFFECT OF EMOTION IN MODERATING THE RELATIONSHIP BETWEEN TAX KNOWLEDGE ON TAX COMPLIANCE - Marlim, Thadeus Nowel (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2023)
Many taxpayers do not comply with tax obligations. There are various reasons why the taxpayer did not fulfill his tax obligations. This study examines the effect of Tax Knowledge on Tax Compliance and the influence of emotions in moderating the relationship between Tax Knowledge on Tax Compliance. This study used a quantitative method in which primary data were obtained from a questionnaire and processed using SPSS. The population in this study is every individual taxpayer in Surabaya who has an income and a Tax ID Number. This study used a purposive sampling technique and obtained 289 samples. The results indicate that Tax Knowledge has a significant effect on Tax Compliance. Emotions can moderate the relationship between tax knowledge and compliance